Prussian Blue Scavenger Ameliorates Hepatic Ischemia-Reperfusion Injury by Inhibiting Inflammation and Reducing Oxidative Stress - Huang, Yongxin; Xu, Qinyuan; Zhang, Jiang; Yin, Yanze; Pan, Yixiao; Zheng, Yuanyi; Cai, Xiaojun; Xia, Qiang; He, Kang (Frontiers in Immunology, 2022)
Oxidative stress and excessive inflammatory responses are the two critical mechanisms of hepatic ischemia-reperfusion injury (HIRI) encountered in many clinical settings, including following hepatectomy and liver transplantation. Effective anti-inflammatory and anti-oxidative pharmacological interventions are urgently needed to counter HIRI. The present study showed that a biocompatible Prussian blue (PB) scavenger with reactive oxygen species (ROS) scavenging and anti-inflammatory properties might be used a promising treatment for HIRI. Following intravenous administration, PB scavenger was mainly distributed in the liver, where it showed excellent ability to alleviate apoptosis, tissue injury and organ dysfunction after HIRI. PB scavenger was found to protect liver tissue by scavenging ROS, reducing neutrophil infiltration and promoting macrophage M2 polarization. In addition, PB scavenger significantly reduced oxidative stress in primary hepatocytes, restoring cell viability under oxidative stress condition. PB scavenger effectively reduced lipopolysaccharide-stimulated inflammation in RAW 264.7 cells. These findings indicate that PB scavenger may be a potential therapeutic agent for the treatment of HIRI, providing an alternative treatment for ROS-associated and inflammatory liver diseases.